Aesthetics and Social Struggle in the Narrative of Ramón Amaya Amador - Barboza-Leitón, Ivannia (2025)
Introduction: The cover of a novel contains mediation in which the design and the illustration are the result of the vision of those who made it. Once approved, it is transformed into a visual narrative constituted by a succession of relations of similarity, disposition or opposition with what it discursively contains. Objective: The paper analyzes a visual corpus of the covers of Prisión verde (editions from 1950 to 2010) and Destacamento rojo (editions from 1962 to 2018) by Ramón Amaya Amador. Methods: According to Genette, paratextuality assumes the existence of a surface on which a cultural text and its subsequent edition are created. This is examined through the variability of images, which determines the reception environment and the represented iconography of banana exploitation. Results: The semiotics of the covers links the predominant aesthetics in the labor representation of the Honduran working class from two perspectives: the self-perception of the problematized situation in Amaya Amador’s narrative and the foreign illustrations, in which the gaze of another alien to the sociohistorical and geographical context in Honduras predominates. Conclusions: Revisiting banana novels from the paratextual element implies an exercise in memory and textuality where representations of the local world and its exploitation are inserted within the narrative discourse of denunciation.